HUBUNGAN ANTARA LAMA MENJALANI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK DI RS GATOEL MOJOKERTO - heni purwati (Akademi Kebidanan Griya Husada Surabaya, 2016)
Hemodialysis therapy in patients with chronic kidney failure can change the physical, psychological, social and economic conditions of the patient because they must be lived for the rest of his life. This can affect the quality of life of patients so that the length of undergoing hemodialysis is one of the factors that affect the quality of life of patients with chronic renal failure. Quality of life is an assessment that focuses on the individual's acceptance of his condition. Every individual needs different time to accept all conditions. The purpose of the study was to determine the relationship between duration of undergoing hemodialysis and the quality of life of patients with chronic kidney failure in Gatoel Hospital, Mojokerto. This study uses a cross sectional design method. The population is chronic kidney failure patients who undergo hemodialysis as many as 150 people. The research sample was taken using nonprobability sampling technique with purposive sampling type of 103 people. Data obtained from KDQoL 36 questionnaire. The results of the study used the Spearman RHO test with the help of SPSS V.16 showing p <? (0.006 <0.05). This means that H0 is rejected so that, there is a relationship between the duration of undergoing hemodialysis and the quality of life of chronic kidney failure patients in Gatoel Hospital, Mojokerto. The quality of life of patients has fluctuations based on the stages of adaptation to hemodialysis and disease. However, most patients undergoing hemodialysis for more than 12 months have sufficient quality of life because patients are familiar with the therapy along with the symptoms and complications they feel. But there are other factors that affect quality of life such as gender, marital status and education level. Patients are also expected to adhere to the recommendations and prohibitions given to improve the quality of life of patients.